NEW TRANSITION-METAL MEDIATED ALKYLATION REACTION OF ARACHNO-S2B7H8, INSERTION REACTION OF ARACHNO-S2B7H8- WITH (CO)5M (C(R1)(R2)) (M=CR, W, R1=CH3, C6H5, R2=OCH3, SC6H5) - SYNTHESIS AND CHARACTERIZATION OF ARACHNO-4-RCH2-6,8-S2B7H8 (R=CH3, IIA, C6H5, IIB) - JEON, HJ; KO, JJ; LEE, KB; KANG, SO (KOREAN CHEMICAL SOC, 1993)
Good yield synthetic routes for the production of new B-alkyl-dithiaborane clusters are reported. The syntheses of the B-alkyl-dithiaboranes are based on the use of Fischer-type carbene reagents to activate the B-H bonds of dithiaborane for alkyl-addition reactions and are the first examples of transition-mediated reactions of dithiaborane to be reported. Thus, reactions employing arachno-S2B7H8- and (CO)5M{C(R1)R2} (M=Cr, W; R1=CH3, C6H5; R2=OCH3, SC6H5) were found to yield the intermidiate anions I, [(CO)5M{C(R1)R2(S2B7H8}]-, which upon protonation gave the corresponding neutral, air-sensitive cluster arachno-4-RCH2-6,8-S2B7H8(R=CH3, IIa; C6H5, IIb) range from 30 to 35% yield. Complexes IIa and IIb are isoelectronic with arachno-6,8-S2B7H9 and, on the basis of the spectroscopic data, are proposed to adopt a similar arachno cage geometry in which an RCH2 units are substituted to 4 position boron atom of the arachno-6,8-S2B7H9.
Keywords: BORON HYDRIDES; PROMOTED REACTIONS; CARBENE COMPLEXES; MONOCARBON CARBORANES; B-ALKENYLBORAZINES; CLUSTERS; BORANES; ALKENYLPENTABORANES; CONVERSION; ALKYNES